The Effects of Taoren-Honghua Herb Pair on Pathological Microvessel and Angiogenesis-Associated Signaling Pathway in Mice Model of CCl(4)-Induced Chronic Liver Disease - Xi, Shengyan (Evid Based Complement Alternat Med, 2016)
Chronic liver disease is one of the most common diseases that threaten human health. Effective treatment is still lacking in western medicine. Semen Persicae (Taoren) and Flos Carthami (Honghua) are known to relieve acute hepatic injury and inflammation, improve microcirculation, and reduce tissue fiber. The aim of our study is to investigate the potential mechanisms of Taoren-Honghua Herb Pair (THHP) in murine model of chronic liver disease caused by Carbon Tetrachloride (CCl(4)). Mice were randomly divided into seven groups: (1) blank, (2) model, (3) control (colchicine, 0.1 mg/kg), (4) THHP (5.53, 2.67, and 1.33 g/kg), and (5) Tao Hong Siwu Decoction (THSWD) (8.50 g/kg). Histological change and microvessels density were examined by microscopy. Hepatic function, serum fibrosis related factors, and hepatic vascular endothelial growth factor (VEGF) were measured with ELISA. VEGF, kinase insert domain-containing receptor (KDR), Flt-1, and Akt mRNA expression in hepatic tissue were determined with PCR. Tissues of Akt, pAkt, KDR, and Flt-1 were measured with western blotting. Data from this study showed that THHP improved hepatic function and restrained the hepatic inflammation and fibrosis. Its role in inhibiting pathological angiogenesis and hepatic fibrogenesis may be through affecting the angiogenesis-associated VEGF and its upstream and downstream signaling pathways.